Accumulation of Microplastics in Agroecosystems and Its Effects on Terrestrial Plants: A Short Review - Islam, Md. Shafiul; Mondal, Shitosri; Angon*, Prodipto Bishnu; Jalil, Md. Abdul (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Microplastics are currently a major global threat as they enter the ecosystem in large quantities daily and are able to persist in the environment for a long period of time. Current research focuses mainly on aquatic and related ecosystems; however, little information is available on the sources, possible accumulation, and pathways of microplastics in agroecosystems. It was previously thought that plastic particles could not be taken up or accumulate in plant bodies, but with modern technology, it has been observed that plastic particles are able to penetrate plants at the micro and nanoscales through transpiration pull forces, and in some cases through the leaves with foliar application. The purpose of the study was to identify potential sources of microplastics, their ways of entry into agroecosystems as well as into plants, and the effects of microplastics on the physiological processes of plants. We highlighted the harmful effects of these pollutants on agricultural ecosystems. Microplastics causes pore space blockages on root surfaces and oxidative damage. Moreover, they inhibit nutrient and water uptake, decrease germination capability, and have negative effects on product quality. Keywords: microplastics; terrestrial plants; agroecosystem; accumulation; oxidative damage *Corresponding author: Tel.: (+880) 1717697088 E-mail: angonbishnubau@gmail.com